TRFill: synergistic use of HiFi and Hi-C sequencing enables accurate assembly of tandem repeats for population-level analysis - Huaming Wen; Jinbao Yang; Xianjia Zhao; Xingbin Wang; Jiawei Lei; Yanchun Li; Wenjie Du; Dongxi Li; Yun Xu; Stefano Lonardi; Weihua Pan (Genome Biology)
Abstract The highly repetitive content of eukaryotic genomes, including long tandem repeats, segmental duplications, and centromeres, makes haplotype-resolved genome assembly hard. Repeat sequences introduce gaps or mis-joins in the assemblies. We introduce TRFill, a novel algorithm that can close the gaps in a draft chromosome-level assembly using exclusively PacBio HiFi and Hi-C data. Experimental results on human centromeres and tomato subtelomeres show that TRFill can improve the completeness and correctness of about two-thirds of the tandem repeats. We also show that the improved completeness of subtelomeric tandem repeats in the tomato pangenome enables a population-level analysis of these complex repeats.